Public Trust in the Perspective of the Role of Actors: What, Why, and How to Improve Public Security and Order - M Awal Chairuddin; Husain Syam; Haedar Akib; Elisatris Gultom; Sulaiman Samad (Technium Social Sciences Journal, 2023)
The results of this research on efforts to improve public trust are based on the implementation of the functions and roles of the Bhayangkara Trustee of Public Security and Order (Bhabinkamtibmas). Actual, acuity, reliable data, information, and knowledge as answers to the questions What, Why, Where, When, Who, and How (5W1H) improve public trust based on the re-actualization of the role of Bhabinkamtibmas actors using descriptive-qualitative research methods with normative approaches and factual approaches. The results of the study found that public trust is a keyword as well as a key success factor in improving the image of individuals and institutions (organizations) of service providers throughout the world, including at the locus of duty and the role of Bhabinkamtibmas in Makassar City, the capital of South Sulawesi Province of Indonesia. Likewise, public trust is a necessity for realizing good governance, and accountable, acceptable, and happy service recipients. Therefore, public trust is a panacea that is effective when individual actors and public institutions at all levels of government, including Bhabinkamtibmas, expect an image of an organization (institution) capable of performing its functions.